Rediseño del sistema de adquisición de datos de radiofrecuencia para la empresa MONITEC, S.A - Víquez-Gómez, Daniel (Instituto Tecnológico de Costa Rica, 2017)
The data collecting and analysis of strategic information, for all the applications this may be useful, is growing in a globalized world that moves thanks to digital and analog communications. The analysis of the information that moves from one side to another, has a vital importance for the strategic decisions that allow to the companies and organizations to take advantage in comparison with those that do not have this information; so, increases their competitiveness. Digitalize the information allows its capture and storage, to make real-time analysis or to store it in databases for later study. Monitoreo Tecnológico company (MONITEC, S.A) emerged in Costa Rica in the year 2000, as a response to the needing of the monitoring electronic media with proper technology to generate reports of this information. The company takes care of providing daily information about all the musical and advertising programming of a territory. The human resources available in the country in terms of technology allow the company to develop technological tools to capture, recognize and monitor electronic and acoustic media. The system created by MONITEC allowed to provide a solution to the problem of low efficiency and low levels of confidence that was obtained with “handmade” monitoring.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2017
Keywords: Adquisición; Datos; Radiofrecuencia; Protocolos; Comunicación serial; Sistemas embebidos; Indicadores; Señales; Ruido; Potencia; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics